2001
DOI: 10.1038/sj.ijir.3900642
|View full text |Cite
|
Sign up to set email alerts
|

Screening of ischemic heart disease with cavernous artery blood flow in erectile dysfunctional patients

Abstract: Erection is a hemodynamic event and accordingly, erectile dysfunction (ED) is closely related with ischemic heart disease. We should con®rm that the cardiac condition of the ED patient is safe enough to perform sexual intercourse prior to beginning treatment for ED. Asymptomatic ischemic heart disease cannot be diagnosed only in an interview, but it's dif®cult to perform cardiac exercise tests on all patients complaining of ED. Therefore, screening methods to evaluate patients who should undergo exercise tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(38 citation statements)
references
References 18 publications
2
34
0
2
Order By: Relevance
“…Another study confirmed our results by showing penile Doppler score to be a more reliable test for the presence of ischemic heart disease than many traditional cardiovascular risk factors. 6 In that study, the mean PSV of the patients without ischemic heart disease was 34.6 vs 22.0 cm/s in those with ischemic heart disease. The sensitivity of PSV against ischemic heart disease was 92.9% and specificity was 59.1%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study confirmed our results by showing penile Doppler score to be a more reliable test for the presence of ischemic heart disease than many traditional cardiovascular risk factors. 6 In that study, the mean PSV of the patients without ischemic heart disease was 34.6 vs 22.0 cm/s in those with ischemic heart disease. The sensitivity of PSV against ischemic heart disease was 92.9% and specificity was 59.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators have reported a higher incidence of abnormal penile blood flow when the patient history includes risk factors such as previous MI, hypertension, or cigarette smoking. 2,4,5 Kawanishi et al 6 showed that men with ED and an abnormal penile Doppler ultrasound exam are at increased risk for ischemic heart disease. 6 To date, there have been few studies assessing the relation between the severity of penile vascular disease and traditional CVD risk factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with low PSV values were more susceptible to IHD than those with normal values. In the study conducted by Kawanishi et al (2001), 1 patients with a PSV value of less than 35 cm/s had a 41.9% incidence of IHD. Our results confirm these findings.…”
Section: Discussionmentioning
confidence: 99%
“…1 Several risk factors are shared by ED and atherosclerotic vascular disease (eg IHD); among these are smoking, hyperlipidemias, hypertension and diabetes mellitus. This observation underlies a common vascular pathology.…”
Section: Introductionmentioning
confidence: 99%